Flood risk management of a polder terminal in Singapore - Loh, Yee (2016)
Singapore is constantly expanding its land area by using land reclamation methods. In order to reclaim land, sand is needed to be dredged and imported from other countries and this has been getting costlier as the years go by. With the increase in price of sand, different methods to reduce the imports of sand are developed with one being the concept of polder terminal. In order for a polder terminal to be constructed, there will be need to conduct flood risk management where all the flooding risks are analysed, assessed and reduced. In Singapore, as polder terminal is a relatively new concept, there is a lack of flood risk management framework. Thus a rough framework will be devised in this report with overtopping and excessive rainfall being focused upon. The flood risk management will go through three primary stages which are: Flood Risk Analysis, Flood Risk Assessment and Flood Risk Reduction. In risk analysis, all the possible problems are identified and briefly discussed. In risk assessment, a deeper understanding of the problems will be generated and the consequences will be identified and assessed by quantifying it in some ways. In risk reduction and assessment of measures, mitigation methods will be identified and the impacts of those methods will be assessed through economic, societal and environmental impact assessments. In order to evaluate and showcase the framework developed, a case study will be used. The area of Tuas in Singapore is chosen as the location of choice. After applying the framework, it was found that the societal consequences are rather insignificant as compared to the economical consequences and total cost. The societal consequences will only be significant when the event mortality is high, the probability of failure is higher and the economical cost is lower. As the probability of failure kept to a minimum for the polder terminal, the societal cost will be small even with the event mortality being very high (20%). Comparisons between costs of normal conventional terminal and polder container terminal are made and the amount of savings from constructing a polder terminal still outweighs the additional risk based on the proposed framework. This thesis merely serves as a reference as overtopping and rainfall are mainly focused upon. More researches may be done for other flood mechanisms in order to have a holistic evaluation of all the risks.